On the integration of manufacturing strategy: deconstructing Hoshin Kanri. Issue 3 (22nd November 2018) - Thürer, Matthias; Maschek, Thomas; Fredendall, Lawrence; Gianiodis, Peter; Stevenson, Mark; Deuse, Jochen
Abstract : Purpose: The purpose of this paper is to show that Hoshin Kanri has the potential to integrate the operations strategy literature into a coherent structure. Hoshin Kanri's planning process is typically described as a top-down cascading of goals, starting with the senior management's goals and moving to the lowest organizational level. The authors argue that this misrepresents a firm's actual cognitive processes in practice because it implies reasoning from the effects to the cause, and assumes a direct causal relationship between what the customer wants and what is realizable by the system. Design/methodology/approach: This study is conceptual, based on abductive reasoning and the literature. Findings: The actual strategic thought process executed in an organization consists of three iterative processes: (i) a translation process that derives the desired customer attributes from customer/stakeholder data, (ii) a process of causal inference that predicts realizable customer attributes from a possible system design and (iii) an integrative process of strategic choices whereby (i) and (ii) are aligned. Each element relies on different cognitive processes (logical relation, causal relation and choice). Research limitations/implications: By aligning the thought and planning processes, the competing concepts of manufacturing strategy are integrated into a coherent structure. Practical implications: Different techniques have to be applied for each of the three elements. As each element relies on different cognitive processes (logical relation, causal relation and choice), the use of unifying tools (e.g. in the form of matrices, as often presented in the literature) is inappropriate. Originality/value: This is the first study to focus on the thought processes underpinning manufacturing strategy.